Penerapan Aplikasi Capcut Untuk Meningkatkan Kreativitas Mahasiswa Institut Agama Islam Uluwiyah Mojokerto - Dwi Indah Nursita (Journal on Education, 2023)
Based on data in the field, the creativity of PGMI students in the 6th semester of IAI Uluwiyah Mojokerto is still relatively low, this can be seen from the lack of focus and enthusiasm of students in participating in the learning process, students easily give up on the material they have just received, many students ignore the lecturer's explanation because of the method. So far, lecturers have been conventional, the learning strategies carried out are centered on the lecturer so that students tend to be passive and feel bored. The aim of this research is to increase the creativity of PGMI IAI Uluwiyah Mojokerto students by implementing the CapCut application to create learning videos. This research is Classroom Action Research (PTK) which was carried out in 2 cycles. From the results of data analysis and discussion, it is concluded that the application of the CapCut application to create learning videos can increase the creativity of PGMI IAI Uluwiyah Mojokerto 6th semester students in the 2022/2023 academic year. The results of observations in cycle 1 showed that student creativity achieved good enough grades with a percentage reaching 65%. In cycle 2, the percentage gain reached 85%. This shows that the increase in student creativity from cycle 1 to cycle 2 increased by 20%.